La comunicación oral en inglés en estudiantes de tercer grado de secundaria según tipo de gestión en instituciones educativas de la zona urbana de Punchana 2020 - Flores Mozombite, Jennifer Crisana (2022)
The objective of this study was to compare third year students’ listening & speaking skills in English in public and private secondary schools at the urban area of Punchana district 2020. The research type was comparative and field study, transectional contemporary and univariable designs. The study population was made up by 585 students and a stratified probability sample with proportional allocation of 232 students. The test results show that the mean score of public-school students was lower than those of private schools (9.92<10.54), as well as in their dimensions: getting information from oral texts (14.72<15.42), inference and interpretation of oral texts (12.55<13.50), use of non-verbal and paraverbal resources (6.44<7.20), strategic interaction (6.04<6.39). In conclusion, the U test of Mann-Whitney for independent samples showed that there are significant differences in listening & speaking skills in English in public and private schools as p-value = 0.007 ? = 0.05, accepting the working hypothesis.